2008
DOI: 10.1556/avet.56.2008.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various dietary fat supplementations on liver lipid and glycogen of high-yielding dairy cows in the peripartal period

Abstract: In a model experiment, Holstein-Friesian dairy cows were fed on a cornsilage-based diet supplemented with 11.75 MJ NE l per day of calcium soaps of palm oil fatty acids (CAS) or hydrogenated triglyceride (HTG) or without fat supplementation (control). All diets were fed to the cows over a period from 21 ± 3 days (d) prior to the expected calving to d 100 ± 5 postpartum. On d 25 (basal sample) and d 14 prepartum as well as on d 5 and 25 postpartum liver samples were collected by percutaneous biopsy. Total lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Our previous animal studies, in mice, demonstrated that the addition of oral α-CD to regular chow diet improved the lipid profile by lowering pro-atherogenic lipoproteins and trans-fatty acids and by decreasing the ratio of saturated and trans-fatty acids to polyunsaturated fatty acids [ 14 ]. In this study, low-density lipoprotein receptor knockout mice were fed a “Western diet” (21 % milk fat) with or without 2.1 % of α-CD (10 % of dietary fat content) for 14 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous animal studies, in mice, demonstrated that the addition of oral α-CD to regular chow diet improved the lipid profile by lowering pro-atherogenic lipoproteins and trans-fatty acids and by decreasing the ratio of saturated and trans-fatty acids to polyunsaturated fatty acids [ 14 ]. In this study, low-density lipoprotein receptor knockout mice were fed a “Western diet” (21 % milk fat) with or without 2.1 % of α-CD (10 % of dietary fat content) for 14 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient demands by the foetus and then lactation reach their maximum in this period, and rising energy demands result in mobilization of fats, protein and other nutrients from body stores (Nielsen & Ingvartsen, 2004; Drackley et al 2005; Ingvartsen, 2006; Fiore et al 2015). Excessive fatty acid mobilization is associated with the development of fatty liver, or deposition of lipid in the hepatic cytoplasm (Karcagi et al 2008). Approximately 40–60% of high-producing dairy cows develop moderate to severe fatty liver during early lactation (Starke et al 2011).…”
mentioning
confidence: 99%
“…Prepartum feeding of canola and sunflower (8% of DMI) is shown to have positive effects on energetic metabolism in postpartum cows, however, the transition from prepar-tum to lactation appeared to be the main driver of changes in energetic metabolism [88]. An interesting study shows that postpartum hydrogenated TG supplementation exerted more positive effects on hepatic lipid and glycogen metabolism than palm oil supplementation [89]. Contrary to high prepartum fat supplementation, postpartum high fat feeding is shown to increase TGs and decrease cholesterol levels, while switching from high prepartum fat to low postpartum fat supplementation increased cholesterol levels, feed intake, and milk production [90].…”
Section: Fatty Livermentioning
confidence: 99%